Organizational innovation in the relationship between total quality management and business financial performance: case of coffee processing firms in Guji zone, Ethiopia - Gemechu Hotessa Warie; Admassu Tesso Huluka; Elfneh Udessa Bariso (Cogent Business & Management, 2024)
The purpose of this study was to investigate the mediation effect of organizational innovation in the relationship between total quality management and business financial performance. The study used a quantitative approach with descriptive and explanatory design. The coffee processing industries were selected based on the type of coffee that they are processing. 334 respondents were involved in the survey using a systematic simple random sampling technique. Descriptive statistical tools frequency distribution, percent, mean and standard deviation were used for analyzing demographic variables. Similarly, the structural equation model was utilized for confirmatory and path analysis. The findings of the study revealed that total quality management has significant and positive effects on business financial performance. Similarly, the results affirmed that organizational innovation partially mediates the relationship between total quality management and business financial performance. The study was limited to the coffee processing industries. Therefore, generalizing the result to other sectors may be questionable and thus, future studies might include other organizations. Similarly, the study was conducted using quantitative data only and further study needs triangulation of results with qualitative data. Overall, the study provided crucial empirical evidence to coffee processing industries, for researchers, academicians and firm managers.
Keywords: 650; Coffee processing; financial performance; guji zone; organizational innovation; total quality management